Analisis Tentang Pentingnya Meningkatkan Kualitas Pendidikan Dalam Shalat - Neriani Neriani; Sri indriyani; Dea Avrilia; Dzakirah Nur Assyifa; Elsa Safitri; Wismanto Wismanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Today, most Muslims are unaware of the meaning and nature of prayer. According to Quraish Shihab, a Muslim who understands the importance and values of education in prayer, his attitude, morals, and way of thinking must also be based on the Qur'an and Hadith. This document tries to examine the importance and importance of prayer for a servant of Allah SWT. Prayer is considered the greatest because prayer also has three human components; The first is gestures, the second is spoken language and the third is the instincts of the heart directed to Allah SWT. All these components can form good morals for a Muslim in dealing with Allah and others. The method used in this research is a qualitative method with a research library approach which uses books, magazines and articles as the main sources. The results of this research show that prayer educates the soul, sharpens the mind, and enlightens the heart through the lantern of the majesty and greatness of Allah SWT which is implanted in the heart. Furthermore, prayer improves behavior and beautifies oneself with noble morals. In addition, prayer protects individuals from committing sins, violations and bad actions that Allah SWT hates